The effect of perceived social support on postpartum stress: the mediating roles of marital satisfaction and maternal postnatal attachment - Yanchi Wang; Jian Gu; Feng Zhang; Xujuan Xu (BMC, 2023)
Abstract Background Multiple factors may be responsible for the development of postpartum stress, including perceived social support, marital satisfaction, and maternal postnatal attachment. However, the underlying mediation mechanisms remain unclear. This study examined the complex relationships between perceived social support and postpartum stress among Chinese women. Methods A convenience sample comprising 406 postpartum women was recruited from six hospitals in Nantong, Jiangsu Province, China. The participants completed general survey questionnaires and were evaluated using the Maternal Postpartum Stress Scale, the Perceived Social Support Scale, the Maternal Postnatal Attachment Scale, and the Marital Satisfaction Scale. Furthermore, we evaluated the relationship between postpartum stress and the various influencing factors by performing a multiple linear regression analysis. The potential mediating roles of marital satisfaction and maternal and infant attachment in the association between perceived social support and postpartum stress were explored by performing a mediation analysis. Results According to the multivariate regression analysis, perceived social support, marital satisfaction, and maternal postnatal attachment contributed to postpartum stress levels (P < 0.05). The mediation analysis revealed that marital satisfaction and maternal postnatal attachment played parallel mediating roles in the association between perceived social support and postpartum stress, and the mediating effect of marital satisfaction was − 0.1125 (95% confidence interval [CI]: -0.1784 to -0.0520), accounting for 33.20% of the total effect, and the mediating effect of maternal postnatal attachment was − 0.0847 (95% CI: -0.1304 to -0.0438), accounting for 25.00% of the total effect. Conclusion Our study revealed that perceived social support could influence postpartum stress not only through direct effect (41.80% of the total effect), but also through the indirect effect (mediation effect) of marital satisfaction and maternal postnatal attachment (58.20% of the total effect), suggesting that improving postpartum women's social support, enhancing maternal and infant attachment, and improving their marital satisfaction could help lower postpartum stress.